2019
DOI: 10.1007/s00484-019-01672-7
|View full text |Cite
|
Sign up to set email alerts
|

Can the development of drought tolerant ideotype sustain Australian chickpea yield?

Abstract: Terminal drought is a major problem in many areas where chickpea is grown on stored soil moisture. This is exacerbated by the lack of a targeted breeding approach focusing on key traits contributing to yield formation under water-limited conditions. There is no study to develop a chickpea ideotype and test it against commercial varieties under various management systems across the Australian grain belt. This study proposed a chickpea ideotype that can be grown in water deficit areas and compared its performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Additionally, the coefficient of determination (R 2 ) and RMSD improved further when the impact of frost events was incorporated into the model (R 2 = 0.70, RMSD = 293 kg/ha) and the observed yields ranged from 784 to 2683 kg/ha; our model adequately predicted this range. Moreover, our coefficient of determination is much higher than 0.6 obtained in another study (Kaloki et al 2019), and our RMSD values are less compared to Robertson et al (2002) and Kaloki et al (2019). This also affirms the improvements in predictions achieved in this study from the re-parameterised APSIM model.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the coefficient of determination (R 2 ) and RMSD improved further when the impact of frost events was incorporated into the model (R 2 = 0.70, RMSD = 293 kg/ha) and the observed yields ranged from 784 to 2683 kg/ha; our model adequately predicted this range. Moreover, our coefficient of determination is much higher than 0.6 obtained in another study (Kaloki et al 2019), and our RMSD values are less compared to Robertson et al (2002) and Kaloki et al (2019). This also affirms the improvements in predictions achieved in this study from the re-parameterised APSIM model.…”
Section: Discussionsupporting
confidence: 88%
“…Relationships among traits were computed using Pearson's simple correlation test, and principal component analysis was performed using Minitab statistical Package 18.0. Ideotypes for yield potential and heat tolerance were then constructed following the approach described by Kaloki, Luo, Trethowan, and Tan (). The data were pooled across years for each environment type to test the genetic variations and yield variations explained by the traits.…”
Section: Methodsmentioning
confidence: 99%
“…Chickpea has a quite limited genetic variation (Varshney 2013), and its wild progenitor (C. reticulatum ) is a rare species with a narrow distribution in a small area of SE Turkey (Abbo et al, 2002). The previous studies screening the collection of Australian chickpea cultivars found that only one genotype (the genotype EF used here) is able to keep early flowering across diverse environments, and flowering time is the most important trait to differentiate the genotype EF from genotypes LF1 and LF2 based on the previous morphological, physiological and genomic comparison (Sadras et al, 2016;Kaloki et al, 2019). Therefore, the differentiation in the root microbiota among the three genotypes in present study was mainly attributed to their phenotypical and genetic variation in flowering phenology, although only one EF genotype was used.…”
Section: Genetic Variation In Phenology Of Host Plants Characterised ...mentioning
confidence: 87%